Pengaruh Kepercayaan, Promosi, Kemudahan, Resiko dan Gaya Hidup Terhadap Keputusan Pembelian Menggunakan Shopee Paylater (Studi Kasus Mahasiswa ITS Mandala Jember) - Hafidhotul Karomah; Haifah; Hamzah Fansury Jusuf (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the influence of trust, promotion, convenience, risk and lifestyle on purchasing decisions using shopee paylater in students of the Mandala Jember Institute of Technology and Science. This study uses a questionnaire distribution method with purposive sampling. The data analysis method uses multiple linear regression analysis with the help of IBM SPSS Statistict 25. The population of this study is students of the Mandala Institute of Technology and Science in 2021. The results of this study show that trust, promotion, and convenience partially have a significant effect on purchase decisions, while risk and lifestyle partially do not have a significant effect on purchase decisions. Simultaneously, trust, promotion, convenience, risk and lifestyle have a significant effect on purchase decisions.